Peranan Kredit Kelompok Petani Kecil Dalam Pembinaan Usaha Sampingan di Kabupaten Deli Serdang dan Langkat - Rahmaniah Rahmaniah; Yusniar Lubis; Azwana Azwana (Universitas Medan Area, 2018)
The purpose of the study was to determine of benefits, the motivation and the loan success factors to farmers at Deli Serdang and Langkat Regencies. The obligation and duty of government as a provider of facilities and services for the community. The services carried out by the department of technical implementation through their respective programs. This coaching program has output that with the formation of a strong institutional groups can be used by farmers to carry out the joint venture. As a result of the joint efforts of farmers have the additional job as a principal side business of work as small farmers. Thus the direct coaching program has helped local governments in providing jobs for small family farmers in the countryside . The studies had the conclusion that the small farmers who are the target P4K program is farmers who are still under the poverty line income that is equivalent to 320 kg of rice per capita per year. Agricultural extension workers have a responsibility to facilitate lending and repayment , so that no group is unrealized arrears due credit. Local governments are expected to provide special assistance fund for poverty alleviation programs and increasing aid channeled through the BRI was appointed to serve small farmers with specific rules and regulations and absolutely no partisanship on the farmers. Keywords : agricultural extension, credit and poverty.